Imaging radial velocity planets with SPHERE. Issue 1 (7th July 2018) - Zurlo, A; Mesa, D; Desidera, S; Messina, S; Gratton, R; Moutou, C; Beuzit, J-L; Biller, B; Boccaletti, A; Bonavita, M; Bonnefoy, M; Bhowmik, T; et al.
ABSTRACT: We present observations with the planet finder Spectro-Polarimetric High-contrast Exoplanet REsearch (SPHERE) of a selected sample of the most promising radial velocity (RV) companions for high-contrast imaging. Using a Monte Carlo simulation to explore all the possible inclinations of the orbit of wide RV companions, we identified the systems with companions that could potentially be detected with SPHERE. We found the most favourable RV systems to observe are: HD 142, GJ 676, HD 39091, HIP 70849, and HD 30177 and carried out observations of these systems during SPHERE Guaranteed Time Observing. To reduce the intensity of the starlight and reveal faint companions, we used principal component analysis algorithms alongside angular and spectral differential imaging. We injected synthetic planets with known flux to evaluate the self-subtraction caused by our data reduction and to determine the 5σ contrast in the J band versus separation for our reduced images. We estimated the upper limit on detectable companion mass around the selected stars from the contrast plot obtained from our data reduction. Although our observations enabled contrasts larger than 15 mag at a few tenths of arcsec from the host stars, we detected no planets. However, we were able to set upper mass limits around the stars using AMES-COND evolutionary models. We can exclude the presence of companions more massive than 25–28 M Jup around these stars, confirming the substellar nature of these RV companions.